Family disposition related to media literacy for advertisements of children's snacks in the media - Angeliqa, Fitria; Sarwono, Billy K. (Penerbit Universiti Kebangsaan Malaysia, 2019)
The study on media literacy generally focuses on content about pornography and violence but does not pay as much attention to advertising. The practical implications of this study are the emergence of critical and analytical attitudes in accepting exposure to children's snack advertisements, especially those containing hazardous materials. This research has theoretical implications in filling the media literacy studies' gap that rarely aims at the content of children's snack advertisements. This study identifies parental—particularly mothers—disposition as part of an effort to literacy in the family. The role of parents is essential for the children's internalization of perspective. Parents can utilize children to understand the messages behind the snack advertisements. Applying the theory of habitus by Pierre Bourdieu, and the concept of street food as a product category of children snacks, and media literacy, this study takes a post-positivist paradigm. The data are obtained from a survey towards 285 parents in five cities in Indonesia (Jakarta, Bogor, Depok, Tangerang, Bekasi), and in-depth interviews were conducted with two mothers who have kids in elementary degree school. The results are the descriptions of dispositions given by the parents to their children relative to snack advertisements so that they can criticize and discuss what snacks should or should not be consumed by children. Furthermore, children have their own set of knowledge and set of attitudes about snacks that can cause health problems.